As morfologias da Cidade Contemporânea: Estruturas e Texturas. Uma matriz interpretativa da forma urbana. O sistema urbano do Porto. - Teresa Manuel de Almeida Cálix Augusto (2013)
The alleged crisis - of the shape, the structure and the limits - of the contemporary city derives from the crisis of the canonical concepts that disclose the reality of urbanization. The common sense idea about the city no longer corresponds to the present-day physical reality. Yet, the differences between the 'ideal city' (historical or traditional) and the unlimited 'other city' are not as significant and profound as those that differentiated, in the past, the city from the countryside. So, more than overcoming the nostalgia of the loss of the 'simple' idea of opposition between the city and the countryside, through the study of the morphologies of the contemporary city what we intend is to demonstrate that what exists today is a widespread urbanization that unfolds in multiple scales, in diversified geographies and in distinctive physical and functional compositions. In fact, urbanization embodies characteristics of different ideologies and models and results of a rational framework of procedures produced in the interaction of society with its territory. The difficulty in understanding these new territories prevents them from being recognized and accepted when the concepts (and analytical instruments) acquired, tested and consensual of the canonical and confined city are no longer the best suited for this new extensive and limitless urbanization. Thus, opposing to the traditionalist streams that insist on the indispensability of universalizing 'rationalization', from which an apparent simplification and arrangement of reality (seen as confuse and incomprehensible) follows, we denounce the complex dimension (not necessarily chaotic) of the existing city and seek to contribute to its understanding through the construction of an interpretative matrix of urban form. Defining such a specific 'way of looking' at the materials of urbanization considers Structures and Textures as its first apparatus of observation. In these circumstances, as the elaboration of a methodological tool corresponds to the central body of this dissertation, the Porto urban system is presented as the empirical space for its operationalization and testing, enabling us to reflect on its theoretical and conceptual consistency. The effort to systematize an interpretive framework of the contemporary urban reality, intended to be generalizable in its use, and not, in the readings resulting of its implementation, aims to contribute to the actual knowledge of each scale and delimitation of the territory. Therefore assuming that reality is built on the concepts that reveal it, undoubtedly it is required to renew the conceptual and theoretical support built for the interpretation of urban models of the past. In conclusion, what inspires this study is the discussion on the principles allowing that new models of city production become legible and intelligible.